Brain Radiation Necrosis Outside the Target Volume After Proton Radiation Therapy: Analyses of Multiparametric Imaging and Proton Biologic Effectiveness - Julianna K. Bronk, MD, PhD; Ahmad Amer; Swapnil Khose, MD; David Flint, PhD; Antony Adair, PhD; Pablo Yepes, PhD; David Grosshans, MD, PhD; Jason Johnson, MD; Caroline Chung, MD, MSc (Advances in Radiation Oncology, 2022)
Purpose: We present the case of a 48-year-old patient with recurrent World Health Organization grade II meningioma in the left occipital region who underwent a subtotal resection, followed by postoperative proton therapy to residual disease and the resection cavity. Fourteen months after radiation treatment completion, surveillance imaging revealed numerous ring-enhancing infratentorial lesions, both within and outside of the high-dose field, of concern for viable tumor. We describe the use of advanced imaging and proton biologic effectiveness analyses to enable the diagnosis of radiation necrosis (RN) and ascertain intrinsic physical factors contributing to the development of RN in this patient. Methods and Materials: Multiparametric magnetic resonance imaging (MRI) and Monte Carlo predictions of linear energy transfer (LET) and variable relative biologic effectiveness dose were performed. Results: The dosimetric analysis revealed that of the 10 lesions, 9 were located outside of the clinical treatment volume and 6 received a dose of <60 Gy relative biologic effectiveness to 95% of the volume. However, increased proton LET values were found in lesions that received lower radiation doses. Dynamic susceptibility contrast and contrast-enhanced, as well as arterial spin labeling-perfusion MRI findings were consistent with RN. Subsequent follow-up imaging revealed no further progression, and the patient was disease-free at the time of this report. Conclusions: We describe a case of brain RN after proton beam radiation outside of the high-dose radiation therapy volume. On initial radiographic detection of these lesions, the distant relationship between their anatomic location with respect to the patient's treatment history reduced the suspicion of RN. However, on closer examination of intrinsic physical variables, RN lesions were present in regions that received a lower dose but higher LETs. Although conventional multisequence MRI was inadequate to distinguish between RN and tumor progression, characterization of tissue physiology allowed for the correct diagnosis, highlighting the utility of advanced brain tumor imaging in the follow-up setting.